INTERNALIZATION OF LOCAL WISDOM VALUE THROUGH I-SPRING TECHNOLOGY-BASED ART AND CULTURE LEARNING - Fatro, Misron Zen; Sulistyo, Edy Tri; Nugroho, Sugeng (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2019)
The social change dynamic in globalization era impacts on the students’ reduced love to local wisdom culture so that they understand poorly the meaning of local wisdom culture existence as cultural heritage rich of life prudence values. This research aimed to analyze the internalization of local wisdom culture values through I-Spring technology-based art and culture learning. The unit of analysis used in this qualitative research with case study approach was stakeholders of SMA Batik 2 Surakarta selected using purposive sampling technique. Techniques of collecting data used were observation, in-depth interview, and documentation. Data validation was carried out using source triangulation, while data analysis was carried out using an interactive model. The result of research showed that I-Spring technology-based art and culture learning could be a learning media facilitating the students to internalize local wisdom culture values. Through I-Spring learning media, students could internalize, externalize, and objectify local wisdom values in order to achieve the balance of students’ conscience, supra-ritual, and intellectuality related to God through the content of local wisdom values. Keywords: Local wisdom, internalization; art and culture learning; i-Spring